Private sector engagement and contributions to immunisation service delivery and coverage in Sudan - Nahad Sadr-Azodi; Nada Ahmed; Denise DeRoeck (BMJ Global Health)
For more than two decades, the private sector in the Sudan (henceforth, Sudan), including non-governmental organisations and for-profit providers, has played a key role in delivering immunisation services, especially in the conflict-affected Darfur region and the most populated Khartoum state. The agreements that the providers enter into with state governments necessitate that they are licenced; follow the national immunisation policy and reporting and supervision requirements; use the vaccines supplied by government; and offer vaccinations free-of-charge. These private providers are well integrated into the states’ immunisation programmes as they take part in the Ministry of Health immunisation trainings and district review meetings and they are incorporated into annual district immunisation microplans. The purpose of this article is to describe the private sector contributions to equitable access to immunisation services and coverage, as well as key challenges, lessons learned and future considerations. Fifty-five per cent of private health facilities in Sudan (411 out of 752) provide immunisation services, with 75% (307 out of 411) based in Khartoum state and the Darfur region. In 2017, private providers administered around 16% of all third doses of pentavalent (diphtheria, pertussis, tetanus, hepatitis B and Haemophilus influenzae type b) vaccines to children. Private health providers of immunisation services have especially been critical in filling the gaps in government services in hard-to-reach or conflict-affected areas and among marginalised populations, and thus in reducing inequities in access. Through its experience in engaging the private sector, Sudan has learned the importance of regulating and licencing private facilities and incorporating them into the immunisation programme’s decision-making, planning, regular evaluation and supervision system to ensure their compliance with immunisation guidelines and the overall quality of services. In moving forward, strategic engagement with the private sector will become more prominent as Sudan transitions out of donors’ financial assistance with its projected income growth.